Predicting growth rates and recessions: assessing US leading indicators under real-time conditions - Jonas Dovern; Christina Ziegler (Kiel Institute for the World Economy (IfW), 2008)
In this paper we analyze the power of various indicators to predict growth rates of aggregate production using real-time data. In addition, we assess their ability to predict turning points of the economy. We consider four groups of indicators: survey data, composite indicators, real economic indicators, and financial data. Almost all indicators are found to improve short-run growth forecasts whereas the results for four-quarter-ahead growth forecasts and the prediction of recession probabilities in general are mixed. We can confirm the result that an indicator suited to improve growth forecasts does not necessarily help to produce more accurate recession forecasts. Only composite leading indicators perform generally well in both forecasting exercises.
Keywords: E37; C32; E32; C25; 330; leading indicators; forecasting; recessions; Konjunkturprognose; Prognoseverfahren; Konjunkturindikator; USA